Thermal analysis of a turbulent wall jet over an adiabatic wavy surface - Kumari A.; Saurabh K.; Kumar A. (My University, 2025)
The impact of wavy wall amplitude on the turbulent characteristics of a wall jet has been investigated experimentally, where the wavy wall is given an adiabatic condition. In the experimental study, the mean and turbulent velocity are measured using a constant temperature anemometer manufactured by Dantec Dynamics. For temperature measurement over the wall and within the flow domain, the FLIR camera and k-type thermocouple are used, respectively. For the current study, uniformly heated at △T0 = (T0 − T∞) = 30 ± 1.2 0C with a Reynolds number of 15,000 is utilized to flow over a sinusoidal wavy wall (y = A*sin (ωx)), where “A = Amplitude ⁄ a” is the amplitude normalised by the nozzle height “a". The nozzle height is 20 mm and to maintain the Reynolds number 15,000 at the inlet, velocity is set at 10.95 ± 0.36 m ⁄ s. The amplitude of the wavy wall is varied between 0.2 and 0.6 and the results are compared to those of the plane wall jet. The current problem is also numerically solved using the k − ε RNG and k − ω SST models. Based on the results, it is concluded that the k − ε RNG model predicts the wavy wall results quite well. It is also discovered that the thermal self-similar profile deviates from the Gaussian curve at the crest of the wavy wall. The influence of the wavy surface on the thermal characteristics of the turbulent wall jet is more pronounced in the near flow field. It is observed that the bottom wall temperature, fluctuating temperature and turbulent heat flux decrease with the increase in amplitude. This indicates that for the higher amplitude, the turbulence increases, which increases the intermixing of jet fluid with the colder ambient fluid. The present results can be used as a benchmark for validating numerical models working in this area. © 2023